About the Cover Image. (1st March 2021) - Allan, Jonathan A.; Haywood, Chris; Karioris, Frank G.
Abstract : On the cover of this issue is an image taken from the Wellcome Collection. Titled "Dance of death: death and the pedlar", the image shows a skeletal personification of Death picking through a basket of goods. In the basket are included masks, crosses, a deck of cards, swords, and a variety of other items. Published in the 18th Century, it is based on, and an interpretation of a piece in Basel on the Dance of Death. It is black and white and a print produced via etching a plate and using this to print the image.